Evaluation of Antibacterial Potential of the Crude Phenolic, Alkaloid and Terpenoid Extracts of Ricinus Communis L. against Gram-negative Pathogenic Bacteria - Hussein J. Hussein (Journal of Global Pharma Technology, 2018)
To uncover the effect of the crude extracts to the phenolic, alkaloid and terpenoid compounds of Ricinus communis L. against some gram-negative Pathogenic Bacteria. Antibacterial activity of the crude Phenolic, Alkaloid and Terpenoid of Ricinus communis L. was determined in vitro using agar well diffusion methods against some gram-negative pathogenic bacteria. Obtained results showed that active compounds of Ricinus communis L. possess wide ranges of antibacterial activity against gram-negative bacteria. This investigation exhibits that we can presume that the effect of active compounds in Ricinus communis L. has a distinctive effect on various pathogenic life forms in various concentrations. Alkaloid compounds extracted from Ricinus communis L. leaves had shown effective antibacterial activity against Escherichia coli, Salmonella and Enterobacter .While, terpenoid compounds it was more effective to Enterobacter, Shegilla and Pseudomonas.Keywords: Antibacterial; Ricinus communis L; Pathogenic Bacteria; Gram-negative Bacteria.